Emotional Reactions and Adaptation to COVID-19 Lockdown (or Confinement) by Spanish Competitive Athletes: Some Lesson for the Future - Jaenes Sánchez, José Carlos; Alarcón Rubio, David; Trujillo, Manuel; Peñaloza Gómez, Rafael; Mehrsafar, Amir Hossien; Chirico, Andrea; Giancamilli, Francesco; Lucidi, Fabio (Frontiers in Psychology, 2021)
The Coronavirus Covid 19 (SARS-CoV-2) has produced terrible effects in world economy and is shaking, social and political stability around the world. The world of sport has obviously has been severely affected by the pandemic, as authorities progressively canceled all level of competitions, including the 2020 Olympic Games in Tokyo. In Spain, the initial government-lockdown closed the High-performance Centers, and many other sports facilities. In order to support athlete´s health and performance at crises like these, an online questionnaire named RECOVID-19, was designed to assess how athletes were living their lives during such periods of home confinement. The main purpose was to assess how such confinement effects impacted on athlete’s psychological, emotional and behavioral. Participants were 1248 athletes (Mean age= 22.31 +- 11.49, Female: 53%), who compete at National (N: 1017, Mean age= 21.58 +- 11.42, Female: 52%) and International level (N: 231, Mean age= 25.56 +- 11.22, Female: 57%). Results showed that at the confinement period, those athletes that lacked motivation had more stressful thoughts and more behavioral problems, reported greater states of emotional upheaval (anger, fatigue, tension, and depression). However, those athletes who believed that confinement measures were necessary and were in favor of respecting the rules of social isolation, fostered positive emotional states such as feelings of friendship. In addition, the availability of some sport equipment and the ability to follow-up some training, were 1) protective factors against emotional stress, lack of motivation and behavioral problems; and 2) they were associated with greater respect for and adherence to the confinement rules. Genders differences were tested by multigroup analysis, results revealed that coping activities were associated to negative emotional states more likely among women, whereas the ongoing availability of training information and future conditions were equally protective factors across both gender groups. In conclusion, this study showed that coaching support and frequent training routines seem to be a valuable tool to prevent some of the harmful effects of isolation on athlete’s emotional well-being. The conclusions of this research would help sport authorities to design supporting plans to the athletes and trainers in case of future disruptive health crises.